THE ANTECEDENTS AND CONSEQUENCES OF WORK ENGAGEMENT ON TEACHER: A SYSTEMATIC LITERATURE REVIEW - Forman Halawa; Elfira Nadya Anggraini; Praptini Yulianti (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
Work engagement is an important study in human resource management related to organizational productivity. Many factors that influence work engagement have been studied. In particular, this study maps the factors that influence work engagement in teachers and the resulting consequences. Contribution made to the literature on work engagement through a description of the antecedents and consequences of work engagement for teachers. This study used the Systematic Literature Review (SLR) method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Eight eligible studies were collected and selected for further analysis. The selected articles were obtained through the Scopus and ScienceDirect databases. The results of the analysis show that there are 12 antecedents of Work Engagement in teachers that come from individual, leadership and organizational factors. It was also found that there are 7 consequences of Work Engagement on teachers that affect the level of teacher involvement in the workplace. The results of the analysis found that the scope of work engagement for teachers differs from various levels of the organization, from elementary schools to tertiary institutions. This study has implications for knowing the antecedents and consequences of Work Engagement on teacher to improve the quality of education.